Promoción digital del turismo de aventura de la Provincia de Los Ríos - GAVILANES RUIZ DAYANNA NAGELLY (2024)
This research is titled "Digital promotion of adventure tourism in the Province of Los Ríos." Digital tourism promotion in Ecuador and the province of Los Ríos must adapt to constant changes and technological advances. The various advantages of technological resources can be exploited for the benefit of adventure tourism advertising marketing, since tourists today spend many hours connected to the Internet. This reflects the trend that more and more users and companies use this medium to obtain information worldwide. It is essential for tourists to obtain experiential information about the different tourist places they can visit. In this way, digital media have become a key factor, causing dizzying changes when choosing your vacation destination or spending a weekend with the family and enjoying the tourist wonders. Therefore, the objective of the research is to propose recommendations to improve the digital promotion of adventure tourism in the Province of Los Ríos, where to fulfill the purpose of the research a methodological design will be used based on the type of non-experimental research of cross section with a qualitative approach of inductive method with a descriptive scope, as a type of research, descriptive research complemented by techniques such as observation and interview combined with instruments such as the observation sheet and the questionnaire of questions that will be validated and approved by the teacher tutor themselves that will allow us to comply with what is established, which is to generate conclusions and recommendations based on the results obtained.